Pengaruh Social Media Marketing terhadap Purchase Intention dengan Brand Awareness sebagai Variable Intervening pada Martha Tilaar Salon Day Spa - Supeni Budi Priatni; Teza Hutriana; Enni Noegraheni Hindarwati (STIE Indonesia Banking School, 2019)
The purpose of this study was to examine the effect of Social Media Marketing variables on Purchase Intention through Brand Awareness. The analysis that be used is path analysis. The sample is 97 instagram followers of Martha Tilaar Salon Day Spa taken from the number of 3721 followers Martha Tilaar Salon Day Spa followers on April 13, 2019. The dependent variable used is Purchase Intention. The independent variable is Social Media Marketing and the intervening variable is Brand Awareness. This study provides empirical evidence that Social Media Marketing has a significant positive effect on Brand Awareness, Brand Awareness has a significant positive effect on Purchase Intention, Social Media Marketing has a significant positive effect on Purchase Intention, Social Media Marketing has a significant positive effect on Purchase Intention with Brand Awareness as an independent variable . Empirical results from this study have implications for salon entrepreneurs, marketing divisions in the beauty and spa industry as well as the development of Social Media Marketing theory, Brand Awareness that influences Purchase Intention as a result of this study